The Impact of Earnings Management on Dividend Policy: Empirical Analysis of Kse-100 Index Firms - Naveed Khan; Dr. Fayaz Ali Shah (Journal of Business & Tourism, 2021)
For a number of purposes management of firms indulges in earnings manipulations. Moreover, to attract investors firms distribute dividend regularly, however sometimes to do so management can manipulate earnings information. in turn, such activities negatively affect the performance of firms in long run. Hence, in current paperinvestigated earnings manipulation and dividend policies of a sample of 76KSE-100 indexnon-financial listed firms ofPakistan stock exchange during2010-2016.Data are secondary in nature and collected from annual reportsof firms.For measurement of earnings manipulation used discretionary accruals of management activities andmodified cross sectional Jones model (1995) is used.Moreover, used random effect panel data techniquefor analysis. The final results revealed that earningsmanagement and dividend payout ratio as proxy of dividend policy are negatively and insignificantly associated. Therefore, concluded that if management involves in manipulation practices then they are unable to pay their obligations as dividend. Moreover, if the governance system is strong then management cannot manipulate true information because according to governance system management should comply and explain the dividend payment procedures.